Androgenetic Alopecia: A Review - Sebastine Oseghae Oiwoh; Ademola Olusegun Enitan; Olubola Titilope Adegbosin; Adeolu Oladayo Akinboro; Emmanuel Olaniyi Onayemi (Nigerian Postgraduate Medical Journal)
This study reviewed the current knowledge on the epidemiology, pathophysiology, clinical presentations, diagnosis, treatment, quality-of-life assessment and recent trends in androgenetic alopecia (AGA). Relevant articles on AGA from PubMed, Google Scholar, Medline and Scopus from 1950 to 2024 were obtained and scrutinized.. Key search words included each term like ‘androgenetic alopecia’, ‘androgenic alopecia’, ‘pattern baldness’ and ‘pattern hair loss’ AND each term like ‘epidemiology’, ‘pathophysiology’, ‘genetics’, ‘hormones’, ‘micronutrient’, ‘stress and inflammation’, ‘growth factors’, ‘clinical features’, ‘staging’, ‘cardiovascular associations’, ‘diagnosis’ and ‘management’ were used in the search. AGA is a non-scarring hair loss that is exemplified by a progressive decline of hair follicles, or non-functional or dead hair follicles in the scalp in a defined pattern. It is the most common hair loss, more common in men but can also present in younger age as premature AGA. Hormones, genetics, micronutrient deficiency, microinflammation and stress have been implicated, while psychosocial distress and cutaneous correlate of cardiovascular diseases have become sources of relentless research. AGA is a patterned hair loss that is more prevalent in Men. It results from the interactions between hormonal, genetic and other factors which determine the extent of hair loss and associated disorders (psychosocial and cardiovascular). As results of more research become available, the extent of AGA, its comorbidities as well as the full spectrum of their manifestations will continue to be sources of health education and more holistic examination by dermatologists and patients.